Analisis Program Bantuan Sosial Pemerintah dalam Meningkatkan Kesejahteraan Masyarakat di Kota Tanjungpinang - Iqnatia Patricia Manalu; Nuranisyah Nuranisyah; Vanny Estperditja br Pinem (Journal of Legal, Political, and Humanistic Inquiry, 2025)
Social assistance programs are strategic public policy instruments in efforts to improve community welfare, especially for poor and vulnerable groups in urban areas such as Tanjungpinang City. This study aims to analyze the role and effectiveness of government social assistance programs in improving community welfare and to identify challenges in their implementation. The research uses a literature study method with a descriptive qualitative approach, with secondary data sources obtained from scientific journals, books, official government reports, social assistance policies, and publications from the Central Statistics Agency. The results and discussion show that social assistance programs such as PKH, BPNT, and BLT contribute positively to meeting basic needs, social protection, and economic recovery of beneficiary households. The effectiveness of the program still faces obstacles in the form of inaccurate targeting, limited validity of beneficiary data, and suboptimal integration of assistance with sustainable economic empowerment programs. The study concludes that improving community welfare through social assistance requires strengthening data collection systems, institutional coordination, transparency in implementation, and policy orientation that is not only protective in the short term but also promotes community independence and long-term welfare.